أثر الامن النفسي على الأداء الوظيفي لدى أساتذة التعليم المتوسط - بن سطال, كنزة رزيقة (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
هدفت هذه الدراسة إلى التعرف على أثر بين الأمن النفسي و الأداء الوظيفي لدى أساتذة المتوسط. و تم وضع الفرضيات التالية:  هل هناك أثر للأمن النفسي على الأداء الوظيفي لدى أساتذة التعليم المتوسط .  ما مستوى الأمن النفسي لدى أساتذة التعليم المتوسط .  ما مستوى الأداء الوظيفي لدى أساتذة التعليم المتوسط .  هل هناك علاقة ذات دلالة إحصائية بين الأمن النفسي و الأداء الوظيفي لدى أساتذة التعليم المتوسط . حيث استهدف البحث إلى التعرف على العلاقة بين الأمن النفسي والأداء الوظيفي لدى أساتذة التعليم المتوسط، حيث استخدم المنهج الوصفي لتحقيق أهداف البحث و قد تضمنت العينة (45) أستاذ و أستاذة في مرحلة التعليم المتوسط بمتوسطتي بن برنومحمد بمستغانم و لخضر بزناينية وادرهيو - غليزان . - ومن أدوات المستخدمة في الدراسة مقياس، الأمن النفسي و الأداء الوظيفي وقد تم استخدام الأساليب الإحصائية باستخدام برنامج spss20 توصلت الدراسة إلى نتائج التالية:  لا يوجد أثر للأمن النفسي على الأداء الوظيفي لدى أساتذة التعليم المتوسط.  مستوى الأمن النفسي لدى الأساتذة التعليم المتوسط لدى أساتذة التعليم المتوسط متوسط.  مستوى الأداء الوظيفي لدى الأستاذة التعليم المتوسط مرتفع.  لا توجد علاقة دالة إحصائيا بين الأمن النفسي و الأداء الوظيفي لدى أساتذة التعليم المتوسط.
دراسة ميدانية لعينة من الاساتذة بمتوسطتي بن برنو محمد مستغانم و مفتاح لخضر بالزناينية بواد رهيو غليزان
This study amied to identify the reeltionship between psychological security and job perfomance among middle school teachers, and the following hypotheses were developed : This study aimed to identify the relationship between shool and the academic achievment of middle school students. - Is there an effect psychological security on the job performance of middle school teachers - what is the level of psychological security among middle school teachers - what is level of job performance among middle school teachres - Is there a statisitically significant reationship between psychological security and job perfomance among midlle school teachers - the research aimed to identify the reationship between psychological security and job perfomance among middle school teachers, where the descriptive approach was used to achieve the research objectives . the sample included 45 male and female teachers in the middle education stage , at Ben Burnou Mohamed midlle school in mostganem and lakhdar moftah midlle school in oued rhiou, relizane state. - Among the tools used in the study were the psychformance scale, and statistical methods were used using the SPSS 20 program. - the study reached the following results :  There is no effect of psychological securtiy on the job perfomance of middle school teachers.  The level of psychological seacurity among middle school teachers is average.  The level of job performance among middle school teachers is high.  There is no statistically significant relationship between psychological security and job performance among middle teachers .
Keywords: الاحتراق النفسي.الاداء الوظيفي.التعليم المتوسط